Physical Activity Based Learning Model for Psychological Well-being of Disabled Students - Warsiyah, Warsiyah; Maisuhetni, Maisuhetni; Khairani, Khairani (Universitas Muhammadiyah Metro, 2024)
This study aims to develop a physical activity-based learning model and test its effectiveness on the psychological well-being of students with disabilities. Using the Research and Development (R&D) method, this study involved 20 students with disabilities (10 males and 10 females) aged 10-15 years from SLB PKK Bandar Lampung. The results of the study show that the learning model developed has the potential to improve the psychological welfare of students with disabilities.